Rising dust pollution across Europe in a changing climate - Petros N. Vasilakos; Abhishek Upadhyay; Manousos I. Manousakas; Andrés Alastuey; James D. Allan; Célia A. Alves; Benjamin Bergmans; Benjamin T. Brem; Sonia Castillo; Theodoros Christoudias; Cristina Colombi; Sébastien Conil; et al. (Nature, 2026)
Abstract Mineral desert dust is a major contributor to total atmospheric particulate matter 1 . Desert dust outbreaks degrade air quality and can pose adverse health effects 2 , including asthma exacerbation 3 and increased mortality 4 . At some European locations, there has been a rise in the intensity and frequency of transported dust outbreaks from deserts in recent decades 5–9 . However, it remains unclear whether this increase is consistent across Europe and whether desertification and aridity or shifts in atmospheric circulation are the main drivers behind this rise. Here we compile a database of daily dust metal concentrations from European sites, establishing robust elemental ratios for transported dust. Using this database, we develop a machine learning model to estimate daily PM 10 (particulate matter smaller than 10 μm) dust concentrations from 2012 to 2021, ranging from 2.09 ± 1.05 μg m −3 across northern and central Europe to 5.28 ± 2.65 μg m −3 across the south. In southern Europe, residents are exposed to transported dust events averaging 9.68 ± 4.85 μg m −3 , linked to a 0.67 ± 0.02% rise in daily mortality. Intensified dust intrusions over the past decade are linked to shifts in atmospheric circulation. Data from an Alpine ice core record shows a 110% increase in dust concentrations since pre-industrial times, mostly associated with North African desertification. As climate change accelerates land degradation and affects weather patterns, worsening dust pollution may pose increasing risks to public health and air quality goals.